Tissue-specific expression of human arylsulfatase-C isozymes and steroid sulfatase. - Munroe, D G (1987)
Steroid sulfatase (STS; E.C.3.1.6.2), which acts on 3-hydroxysteroid sulfates, and arylsulfatase-C (ARC; E.C.3.1.6.1), assayed with aromatic artificial substrates, are both membrane-bound, microsomal enzymes with alkaline pH optima. Although they copurify during preparation and their gene loci are mapped to the short arm of the human X chromosome where they appear to have escaped from X inactivation, it has not been settled whether STS and ARC are the same enzyme or not. Recent work from our laboratory has shown that ARC exists in two electrophoretically distinct forms in human fibroblasts. We now report that these two forms--the faster migrating (F) and more slowly migrating (S)--occur in human tissues. Each of 11 human tissue types from 10 subjects showed a consistent pattern of ARC isozymes. Thyroid, heart, spleen, skeletal muscle, and adrenal tissue mainly had the S form. In contrast, kidney, liver, and pancreas tissue had mainly the F form, while gonadal, lung, and intestinal tissue had both the S and the F forms. The question of escape of their gene locus from X-chromosome inactivation was examined by comparing the specific activities of ARC and STS in male-derived vis-à-vis female-derived tissues. The majority of the tissues did not show any significant difference in these activities between the sexes, the exceptions being heart muscle, gonadal, and kidney tissue. None showed the 1:2 ratio between male- and female-derived tissues expected of a locus that had escaped X inactivation. The question of identity between ARC and STS was examined by comparing the ratios of their activities in these tissue types: if the enzymes were identical, the ratios of their activities should have remained constant across the different tissue types. It was thus shown that ARC activity varied by as much as 100-fold, depending on the ARC isozymic pattern of the tissue. STS, measured as estrone sulfatase and dehydroepiandrosterone sulfatase, did not show similar variations. This provides further evidence that ARC activity is not necessarily identical to that of STS.